Integrative Nanomedicine: treating Cancer with Nanoscale Natural Products. Issue 1 (January 2014) - Bell, Iris R.; Sarter, Barbara; Koithan, Mary; Banerji, Prasanta; Banerji, Pratip; Jain, Shamini; Ives, John
Finding safer and more effective treatments for specific cancers remains a significant challenge for integrative clinicians and researchers worldwide. One emerging strategy is the use of nanostructured forms of drugs, vaccines, traditional animal venoms, herbs, and nutraceutical agents in cancer treatment. The recent discovery of nanoparticles in traditional homeopathic medicines adds another point of convergence between modern nanomedicine and alternative interventional strategies. A way in which homeopathic remedies could initiate anticancer effects includes cell-to-cell signaling actions of both exogenous and endogenous (exosome) nanoparticles. The result can be a cascade of modulatory biological events with antiproliferative and pro-apoptotic effects. The Banerji Protocols reflect a multigenerational clinical system developed by homeopathic physicians in India who have treated thousands of patients with cancer. A number of homeopathic remedy sources from the Banerji Protocols (eg, Calcarea phosphorica; Carcinosin—tumor-derived breast cancer tissue prepared homeopathically) overlap those already under study in nonhomeopathic nanoparticle and nanovesicle tumor exosome cancer vaccine research. Past research on antineoplastic effects of nano forms of botanical extracts such as Phytolacca, Gelsemium, Hydrastis, Thuja, and Ruta as well as on homeopathic remedy potencies made from the same types of source materials suggests other important overlaps. The replicated finding of silica, silicon, and nano-silica release from agitation of liquids in glassware adds a proven nonspecific activator and amplifier of immunological effects. Taken together, the nanoparticulate research data and the Banerji Protocols for homeopathic remedies in cancer suggest a way forward for generating advances in cancer treatment with natural product–derived nanomedicines.